Strength-based parenting and life satisfaction in teenagers - Waters, Lea E (Advances in Social Sciences Research Journal, 2015)
Two studies demonstrated the positive associations that authoritative parenting and strength-based parenting have with life satisfaction in adolescents. In Study 1, teenagers’ (N = 689; Mage = 15.20, SD = 3.80; 52% male) reports of the degree to which their parents demonstrated authoritative and strength-based parenting (SBP) explained over a third of the variance in life satisfaction scores (Adj. R2 = 35%). SBP explained 19% of variation in life satisfaction scores above and beyond the effects of authoritative parenting. Furthermore, SBP prospectively and significantly predicted 5% of life satisfaction in teenagers 12 months later. Study 2 recruited 127 adolescent-parent dyads (Adolescent Mage 15.30, SD = 2.30; 58% female; Parent Mage = 46.01, SD = 11.02; 67% mothers) and found that parent-reports of the degree to which they are aware of their son/daughter’s strengths and the degree to which they encouraged their son/daughter to use their strengths explained additional variance in life satisfaction in adolescents beyond their adolescent son/daughter’s own strengths-knowledge and strengths-use. It was concluded that strength-based parenting is a significant contributor to life satisfaction during adolescence.